Breast Reconstruction Using the Lateral Thoracic, Thoracodorsal, and Intercostal Arteries Perforator Flaps. Issue 1 (January 2021) - Mangialardi, Maria Lucia; Baldelli, Ilaria; Salgarello, Marzia; Raposio, Edoardo
Abstract : Background: Breast-conserving surgery followed by radiotherapy represents the standard of care for early-stage breast cancer. The aim of this article was to provide a review of the literature about the use of the lateral thoracic artery perforator (LTAP) flap, the lateral thoracodorsal (LTD) flap, and the lateral intercostal artery perforator (LICAP) flap in lateral partial breast defect. Methods: A literature search was performed via PubMed, Medline, and Cochrane. Patient's characteristics, topography and size of breast defect, flap size and design, number of perforators, and operative time were analyzed. Aesthetic and patient-reported outcomes, postoperative complications, and donor site morbidity were also registered. Results: Thirteen articles fulfilled inclusion criteria, and 432 patients were included. Different flap designs and flap combinations were described. Satisfactory outcomes were reported for between 78% and 100% of cases. Patient satisfaction ranged from 75.8% to 92.5% of cases. The overall complication rate was 9.25%, and donor site morbidity was very low (3.7%). Conclusions: A distinct advantage of LTAP, LTD, and LICAP flap reconstruction is that the thoracodorsal pedicle is not sacrificed, not compromising eventual delayed breast reconstruction with TDAP or latissimus dorsi flaps. This staged approach to partial breast reconstruction is especially useful in cases where the oncological margins are uncertain and wider resections (or mastectomies) are secondly required.